PENGEMBANGAN SEDIAAN TABLET ESTROGENIK DARI EKSTRAK RUMPUT KEBAR (Biophytum petersianum) MENGGUNAKAN VARIASI KONSENTRASI PENGIKAT PVP K-30 - Erni Rustiani; Dania Triska Puspita; Wilda Nurhikmah (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Kebar grass (Biophytum petersianum Klotzsch) contains steroid, saponins, flavonoids, alkaloids, and triterpenoids. The use of Kebar grass extract can increase the development of follicles because it contains saponins which are the basic ingredients for the synthesis of steroid hormones and can improve the performance of reproductive system. This study aims to determine the quality the tablets made from Kebar grass extract with varying concentrations of PVP K-30 binder. Tablets were made in 3 formulas with varying concentrations of PVP K-30 as a binder, namely 2% (F1), 3% (F2), and 4% (F3). Methods of making tablets by wet granulation. Tablet quality testing includes organoleptic, weight uniformity, thickness, diameter, hardness, friability, and disintegration time. The flavonoid quercetin was used as a marker for tablet analysis. The results showed that the tablets were round in shape, white-gray in color, had a slightly bitter taste and had a characteristic aromatic odor. The average value of tablet weight uniformity is 290.06 – 306.45 mg (KV <5%), tablet diameter is 0.91 -0.92 cm, thickness is 0.41 – 0.48 cm, hardness is 4.06 – 7.95 kp, friability 0.17 – 0.21% and tablet disintegration time < 15 minutes. The results of the statistical analysis showed that the differences in the concentration of PVP K-30 did not affect the hardness and friability of the tablets (p> 0.05). The level of the flavonoid quercetin in the tablet is 0.17 – 0.21%. The conclusion that Kebar grass extract tablets can be made using PVP K-30 at a concentration of 2-4% as a binder and the quality of the tablets is not significantly different.